Producing knowledge about Malaya : readers, contributors, printers, editors, and the journal of the Malayan branch of the Royal Asiatic Society in the 1950s - Luyt, Brendan (2012)
The creation and dissemination of knowledge about the various parts of the British Empire was an important component of the imperial mission. This article examines one of the vehicles charged with knowledge dissemination in British Malaya, the Journal of the Malayan Branch of the Royal Asiatic Society. More specifically it focuses on the community of contributors, readers, printers, and editors that came together around the publication in the 1950s, the twilight of British rule on the peninsula. We can look at this community as a fragile web of elements or actors responsible for producing the Journal, which over the course of the decade rapidly began to unravel for a number of reasons (difficulties in conducting local research, a decline in the number of contributors as the British colonial officials left the country without being replaced, delays in publication, and a lack of skilled printers, among others) so that by the 1960s there was some doubt that the publication would survive.